Tổ chức và hoạt động của thanh tra nhân dân - Phạm, Hưng (2011)
Tác giả: Phạm Hưng, CN; Vũ Như Ngô, CN; Nguyễn Hữu Đàn, CN; Hoàng Văn Nhiệm; Phạm Viết Khẩn, CN; Phan Minh, CN; Lê Văn Võ, CN; Vũ Minh Hồng, CN; Lê Văn Hải, CN; Nguyễn Bá Thu, CN -- Từ khóa: Thanh tra; Thanh tra nhân dân; Tổ chức; Hoạt động; Pháp luật